2018
DOI: 10.1371/journal.pone.0193325
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of extended spectrum beta-lactamase-producing enterobacteriaceae in neonates: A community based cohort in Madagascar

Abstract: In low and middle income countries (LMICs), where the burden of neonatal sepsis is the highest, the spread of extended spectrum beta-lactamase-producing enterobacteriaceae (ESBL-PE) in the community, potentially contributing to the neonatal mortality, is a public health concern. Data regarding the acquisition of ESBL-PE during the neonatal period are scarce. The routes of transmission are not well defined and particularly the possible key role played by pregnant women. This study aimed to understand the neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 61 publications
0
28
1
3
Order By: Relevance
“…In Cambodia, young hospital-born infants were found to be at a greater risk of early colonization by third-generation cephalosporin-resistant gram-negative rods compared to infants born at home, a health center, or other locations and subsequently admitted to hospital [20]. In Madagascar, Herindrainy et al reported that low birth weight, cesarean delivery, and use of antibiotics by mothers at delivery were independently associated with neonatal acquisition of ESBL-E during the first month of life [21].…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, young hospital-born infants were found to be at a greater risk of early colonization by third-generation cephalosporin-resistant gram-negative rods compared to infants born at home, a health center, or other locations and subsequently admitted to hospital [20]. In Madagascar, Herindrainy et al reported that low birth weight, cesarean delivery, and use of antibiotics by mothers at delivery were independently associated with neonatal acquisition of ESBL-E during the first month of life [21].…”
Section: Discussionmentioning
confidence: 99%
“…In case of C-section for example, the newborn is not exposed to maternal microbiota that may confer protection against ESBL colonization. 37,38 In addition, delivery in a potentially septic context (maternal fever, prolonged rupture of membranes etc.) has been shown to increase infant ESBL colonization risk, consistent with potential vertical transmission from mother to child.…”
Section: Discussionmentioning
confidence: 99%
“…Herindrainy P. y cols. 24 , reportaron que el uso de antimicrobianos durante el embarazo favorece la infección neonatal por enterobacterias maternas productoras de BLEE (HR 2,2; IC 95% 1,1-4,5).…”
Section: Discussionunclassified
“…Herindrainy P y cols. 24 , detectaron colonización intestinal por EP-BLEE en 19,6% de las madres, mientras que Strenger V y cols. 28 , la identificaron en 18,4%.…”
Section: Discussionunclassified